THE EFFECT OF THE WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE IN THE BERINGIN DISTRICT OFFICE OF DELI SERDANG REGENCY - Fatimah Pohan; Rahimah Angkat (Teunuleh Publisher, 2022)
Beringin District is one of the sub-districts in Deli Serdang Regency, has a Vision of